The Relationship between Self-Confidence and the Social Interaction Ability of Broken Home Students - Nadya Agustin; Taufik Taufik (Universitas Negeri Padang, 2024)
This research is motivated by the large number of students from broken homes who have difficulty interacting socially at school. This difficulty will affect their learning success. The ability to interact socially is influenced by a number of factors, including the level of self-confidence. This study aims to describe the self-confidence and social interaction abilities of broken home students, and to reveal the relationship between self-confidence and the social interaction abilities of broken home students. This study uses a quantitative method with a descriptive correlational approach. The population of the study was 100 students from broken homes with a sample of 60 people selected using a purposive sampling technique. The instruments used were self-confidence and social interaction ability questionnaires. Data were analyzed using descriptive analysis techniques and using the Pearson Product Moment Correlation formula. The results of the study showed that: (1) the average score of self-confidence achievement of students from broken homes was 62.52 (45.51%) and most students had low self-confidence, (2) the average score of social interaction ability achievement of students from broken homes was 70.03 (47.62%) and most students had low social interaction ability, and (3) there was a significant positive relationship between self-confidence and the social interaction ability of students from broken homes with a correlation of 0.655.